The Role of Community Benefits on Brand Loyalty in Automotive Social Media Brand Community - Puspita Pratama Novianti; Tengku Ezni Balqiah (Universitas Airlangga, 2023)
Objective: This study examines the benefits of online brand community interactivity in social media in the Indonesian automotive sector. Design/Methods/Approach: The proposed model was empirically assessed using survey data from 332 Indonesian-based automobile online brand community members on social media. In addition, the link between the constructs in the research model was examined using SEM PLS. Findings: The findings strongly link perceived interactivity and community benefits. In Addition, the results also demonstrate that community members' trust in a brand strongly and positively impacts brand loyalty. Special treatment and a sense of membership increase members' trust in the brand and community satisfaction. However, social influence has negligible effects on community satisfaction. Originality/Value: This study combines value, trust, and satisfaction as the mediating variables in the relationship between interactivity in the online community and loyalty. Practical/Policy implication: Given the results, brands should provide flexibility to access information or content by optimizing the usage of social media features that members can easily access anytime, such as adding links to the Instagram bio or description on Facebook or WhatsApp groups. Enhancing these community benefits can be done by ensuring that the information circulated within the community is accurate and informative.